2014
DOI: 10.1186/1471-244x-14-190
|View full text |Cite
|
Sign up to set email alerts
|

Adult depression screening in Saudi primary care: prevalence, instrument and cost

Abstract: BackgroundBy the year 2020 depression would be the second major cause of disability adjusted life years lost, as reported by the World Health Organization. Depression is a mental illness which causes persistent low mood, a sense of despair, and has multiple risk factors. Its prevalence in primary care varies between 15.3-22%, with global prevalence up to 13% and between 17-46% in Saudi Arabia. Despite several studies that have shown benefit of early diagnosis and cost-savings of up to 80%, physicians in primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
145
7
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(164 citation statements)
references
References 36 publications
11
145
7
1
Order By: Relevance
“…Comparable findings were reported in the U.S. National Comorbidity study, which observed that women had elevated rates of affective disorders and anxiety disorders whereas men had elevated rates of substance-use disorders and antisocial personality disorder 27 . Also, similar findings were reported in European studies 28,41 and a local primary care study 42 . Although the evidence of gender differences in the risk of schizophrenia is inconclusive, a meta-analysis observed the that men have a higher incidence and morbidity risk than women 43 .…”
Section: Discussionsupporting
confidence: 74%
“…Comparable findings were reported in the U.S. National Comorbidity study, which observed that women had elevated rates of affective disorders and anxiety disorders whereas men had elevated rates of substance-use disorders and antisocial personality disorder 27 . Also, similar findings were reported in European studies 28,41 and a local primary care study 42 . Although the evidence of gender differences in the risk of schizophrenia is inconclusive, a meta-analysis observed the that men have a higher incidence and morbidity risk than women 43 .…”
Section: Discussionsupporting
confidence: 74%
“…In this study, the prevalence of depression was 46% and 42% for the anxiety. The rates of depression and anxiety were much higher than that reported in primary care setting in Saudi Arabia, which was 18.8% for depression41 and 5.3% for anxiety disorder 42…”
Section: Discussioncontrasting
confidence: 54%
“…The rate was lower than that reported in Riyadh (18.8%) and Kuwait (20.5%) [12,13] and higher than in Qatar (13.5%, 2010). [14] Similar studies conducted in European countries revealed a prevalence rate ranging from 16.5% to 22.8%, [15][16][17] indicating that the rates in Gulf Region are comparable with those of Europe.…”
Section: Discussioncontrasting
confidence: 49%
“…[10,11] The scale consists of nine questions, for which the answers ranged from ''not at all'' (given a score of 0) to ''nearly every day'' (given a score of 3) experiencing the symptom within the last 2 weeks. The total score was calculated and categorized into no depression (0-4), mild depression (5-9), moderate depression (10)(11)(12)(13)(14), and severe depression (15+). Weight and height were also measured for 836 participants (with a response rate of 98.4%), and body mass index (BMI) was calculated and categorized into underweight (less than 18.5 kg/m 2 ), normal weight (18.5-24.9), overweight (25-29.9), obesity (30-34.9), and severe obesity (more than 35 kg/m 2 ).…”
Section: Methodsmentioning
confidence: 99%